2018
DOI: 10.21608/ejm.2018.5057.1072
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Detection of Antibacterial Activity of Glycyrrhizic Acid Nanoparticle against ESBL Producing Klebsiella pneumoniae Strains

Abstract: E XTENDED-spectrum β-lactamase (ESBL) producing Klebsiella pneumoniae strains can present resistance to many antibiotic groups due to resistant genes. This study conducted to detect and identify multi-drug resistant (MDR), ESBL producing K. pneumoniae strains from different clinical samples with detection and sequencing of both Temoneira (TEM) and sulfhydryl variable (SHV) genes and using Glycyrrhizic acid nanoparticle as an antimicrobial agent for ESBL producing K. pneumoniae strains. One hundred and fifty cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A study in Egypt revealed 46 E. coli isolates and showed that all extended-spectrum beta-lactamase (ESBL) producers were positive for bla CTX-M and bla TEM genes [ 53 ]. Another study carried out on K. pneumoniae showed that bla CTX-M and bla TEM genes were detected in 52.8% and 53.3% of ESBL isolates, respectively [ 54 , 55 ]. In another study, bla CTX-M and bla TEM genes were detected in K. pneumoniae more frequently than E. coli , and bla TEM genes were detected more frequently than bla CTX-M [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Egypt revealed 46 E. coli isolates and showed that all extended-spectrum beta-lactamase (ESBL) producers were positive for bla CTX-M and bla TEM genes [ 53 ]. Another study carried out on K. pneumoniae showed that bla CTX-M and bla TEM genes were detected in 52.8% and 53.3% of ESBL isolates, respectively [ 54 , 55 ]. In another study, bla CTX-M and bla TEM genes were detected in K. pneumoniae more frequently than E. coli , and bla TEM genes were detected more frequently than bla CTX-M [ 38 ].…”
Section: Discussionmentioning
confidence: 99%